Implementation of Therapeutic Patient Education (TPE) in Primary Care, as Perceived by Professionals: A Narrative Review - Kirkove D; Durieux N; Allory E; Louis G; Gagnayre R; Pétré B (Patient Preference and Adherence)
Delphine Kirkove,1,2 Nancy Durieux,3 Emmanuel Allory,2,4,5 Gilles Louis,1,6 Rémi Gagnayre,2,* Benoit Pétré1,* 1Department of Public Health, University of Liège, Liège, Belgium; 2Université Sorbonne Paris Nord, Laboratory Educations and Promotion of Health, UR 3412, Villetaneuse, F-93430, France; 3Research Unit for a life-Course perspective on Health and Education (RUCHE), University of Liège, Liège, Belgium; 4Department of General Practice, University of Rennes 1, Rennes, F-35000, France; 5CIC (Clinical Investigation Centre) Inserm 1414, Rennes, F-35000, France; 6GIGA I3, Department of Clinical Sciences, Pneumology, University of Liège, Liège, Belgium*These authors contributed equally to this workCorrespondence: Delphine Kirkove, Department of Public Health, University of Liège, Liège, Belgium, Tel +323662305, Email delphine.kirkove@uliege.beAbstract: Therapeutic patient education (TPE) has proven an effective approach to managing chronic diseases. Despite its proven effectiveness, TPE is mainly found in health care structures and has little presence in primary care. This study aimed to identify the obstacles and facilitators to applying TPE in primary care settings for chronic disease management. A systematic narrative review was conducted using three databases: Medline (Ovid), Scopus, and Embase, following the tool’s recommendations Scale for the Quality Assessment of Narrative Review Articles (SANRA). Data were analyzed using the Patient Education Research Characteristics (PERC) grid and the Theoretical Domains Framework (TDF). The review included 12 articles, revealing that TPE practices in primary care are often underdeveloped, primarily individual, and focused on oral, informative methods. Obstacles identified by healthcare professionals primarily fall into two TDF domains: environmental context (eg, lack of time, resources, and fragmented healthcare systems) and individual skills deficits. Stress and tension were also noted as significant challenges. Conversely, facilitators included social factors, such as shared team values, strong managerial support, and the presence of a TPE referent, as well as community of practice support. The results of this narrative review show that the development of TPE requires both functional resources, such as funding, but also a normative integration based on the sharing of common values and norms in primary care. It is essential to take into account all the factors identified, while mobilizing the environment as a resource and involving primary care professionals in a co-construction process.Keywords: therapeutic patient education, TPE, primary care, implementation, obstacles, facilitators